2016
DOI: 10.1039/c6tb02574a
|View full text |Cite
|
Sign up to set email alerts
|

Developing Mn-doped lead sulfide quantum dots for MRI labels

Abstract: Magnetic interactions of Mn2+ ions in lead sulfide (PbS) nanocrystals with protons in water are probed by NMR and MRI. A thin layer of capping molecules enables free solvent diffusion to the nanocrystal surface resulting in a decrease of proton relaxation times. Magnetic resonance imaging of neuronal cell pellets exposed to (PbMn)S at non-toxic concentrations demonstrates their prospects as MRI-labels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Over the past decade, lead sulfide (PbS) has received increasing attention in the field of photodetectors because of its unique electronic properties . Until very recently, PbS was investigated in biomedical research for use as computer tomography (CT) and fluorescence contrast agents because of the features of high atomic number, , admirable X-ray absorption, and excellent NIR absorption . For example, Liu et al prepared PbS nanodots by using l -glutathione reduced as a stabilizing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, lead sulfide (PbS) has received increasing attention in the field of photodetectors because of its unique electronic properties . Until very recently, PbS was investigated in biomedical research for use as computer tomography (CT) and fluorescence contrast agents because of the features of high atomic number, , admirable X-ray absorption, and excellent NIR absorption . For example, Liu et al prepared PbS nanodots by using l -glutathione reduced as a stabilizing agent.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the contrast agents are visible on both T 1 - and T 2 -weighted images, which grasp more attention due to functioning as dual-mode contrast agents in MRI. , For instance, manganese (Mn 2+ )-doped silica nanoparticles, , Mn-doped nanoparticles, Mn-doped sulfide quantum dots, and (Mn)–ND conjugates have demonstrated the dual mode contrast enhancement in MRI imaging due to Mn’s characteristic property of displaying the T 1 – T 2 dual-mode contrast ability. , However, Mn has an adverse effect on biocompatibility due to its toxicity on cardiotoxicity and neurodegenerative effects. , Even though Mn chelates and conjugates were utilized as MRI contrast agents due to their low toxicity and desired relaxivity. ,, In addition, according to our best knowledge, very few studies have been reported on Mn-ND-based MRI contrast agents, especially one study that reported ND-Mn dual-mode contrast enhancement for liver tumor detection . In addition, the Mn chelates or conjugates are prepared by chemical methods and have the probability of leaching during MRI imaging and causing the related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Mn 2+ has lower toxicity, exhibits a relaxivity similar to that of Gd 3+ and has been demonstrated to be a valuable alternative as a dopant to Gd 3+ for engineering nanocrystals for bimodal imaging. Binary CdS, PbS, ZnS, , and ZnSe, ternary In–Zn–S, and quaternary Cu–In–Zn–S (CIZS) and Cu–In–Zn–Se (CIZSe) QDs have successfully been doped with Mn 2+ ions for combined PL and MR imaging.…”
Section: Introductionmentioning
confidence: 99%
“…25 Mn 2+ has lower toxicity, exhibits a relaxivity similar to that of Gd 3+ and has been demonstrated to be a valuable alternative as a dopant to Gd 3+ for engineering nanocrystals for bimodal imaging. Binary CdS, 26 PbS, 27 ZnS, 28,29 and ZnSe, 30−32 ternary In−Zn−S, 33 We recently reported the synthesis of highly luminescent quinary Ag−In−Ga−Zn−S (AIGZS) QDs via thermal decomposition in oleylamine (OAm) of a single Ag x In y Ga 2−x−y Zn 2 (S 2 CN(C 2 H 5 ) 2 ) 4 dithiocarbamate precursor. 37 In this study, we used the heavy-metal-free AIGZS QDs as host nanocrystals to incorporate Mn 2+ dopants, and the dual functional (PL/MRI) properties of the doped QDs were investigated.…”
Section: Introductionmentioning
confidence: 99%